Wykorzystanie mobilnych agentów programowych w elektronicznym rejestrze usług medycznych - Wasiak, Maciej (Mobile Agents in Polish Health Care System, 2006)
The main aim of introducing complex information systems into public health care system is to reduce number of frauds. The most popular conception considers distributed architecture with many servers collecting necessary data. In such architecture, methods like OLAP or even data mining can turn out to be useless or, at least, not efficient enough. In the paper, typical methods of medical fraud detection are presented and a mobile agents technology is proposed, as the promising tool for this purpose.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 180-189